POLYETHERETHERKETONE IN DENTAL IMPLANTS. A REVIEW. - Anca Vițalariu; Monica Tatarciuc; Diana Diaconu‐Popa; Irina Chonta; Celina Silvia Stafie (Romanian Society of Oral Rehabilitation, 2021)
Polyetheretherketone (PEEK) is a polymer that has been used for several decades in engineering, but later entered the medical field. Being a biocompatible material and because it has shown resistance to in vivo degradation, it was launched in 1998 as a biomaterial for implants intended for long-term use. PEEK has demonstrated that it is a high performance thermoplastic polymer, capable of replacing implant metal components, initially in the field of orthopedics. These findings suggested that PEEK could also replace titanium for dental implants. PEEK applications in dentistry are diverse, from crowns, bridges and removable dental prostheses to dental implants. The material comes in the form of discs that will be milled using CAD-CAM technology, but can be processed by various techniques, including injection molding, and extrusion. The manufacturers claim that these devices have very good mechanical properties, easier work with than ceramics and titanium, and can be applied to patients with allergies.